Effects of ecological factors on phytochemical and nutritional composition of Caralluma tuberculata N. E. Brown. (December 2022) - Ullah, Irfan; Adnan, Muhammad; Begum, Shaheen; Nazir, Ruqia; Javed, Tehseen; Aziz, Muhammad Abdul
Abstract: The effects of global warming on vegetation phenology are widespread. A study in Southern Khyber Pakhtunkhwa, Pakistan investigated the effects of ecological factors including precipitation and temperature on phytochemical, and nutritional composition of wild Caralluma tuberculata N. E. Brown. Photosynthetic pigments, saponins, crude proteins, crude fats, moisture, and ash were significantly higher ( p  < 0.05) in the plants of Shaker Darra area than in the plants of Lakki Marwat, Darra Adam Khel, and Spin Wam areas. Pearson correlation explains a high correlation existing between the annual rainfall and temperature with that of pregnane glycosides. The current study concluded that mainly rainfall influences the phytochemical, nutritional, and physiological profiles of C. tuberculata . Highlights: C. tuberculata, a locally vulnerable multipurpose plant species. Rainfall affects photosynthetic pigments and phyto-chemicals of C. tuberculata . Temperature also alters phyto-chemical and nutritional composition.